The feasibility of transference between native language and foreign language regarding reading strategies - Aydın, Semih (My University, 2003)
The present study investigated the effect of reading strategy instruction in L1 (Turkish) and L2 (English) on L1 and L2 reading comprehension performance of learners, and the feasibility of transference between L1 and L2 reading processes regarding reading strategy awareness and use. Forty male students from the senior class a free boarding segregated government high school at intermediate proficiency level at English as a Foreign Language constituted the participants of the study. The participants were randomly marked as a Control Group and Experimental Group each of which equally had twenty students. During the treatment period the control group was instructed on reading strategies only in English while the experimental group was simultaneously given an identical strategy training both in English and Turkish. The data was collected through a Personal Background Information Questionnaire and a Reading Habits and Preferences Questionnaire given prior to the treatment, and Self-Evaluation Charts of Reading Strategy Use in L1 and L2 reading, Turkish Reading Comprehension Tests, and English Reading Comprehension Tests given both before and after the treatment. The results of the reading comprehension tests were analyzed by means of the Statistical Package for the Social Sciences (SPSS, version 10.0) using dependent and independent group T-tests, while the data collected through the questionnaires and self-evaluation charts were computed manually. The findings of the study indicated that the subjects of the experimental group who were given reading strategy instruction in L1 achieved a statistically significant gain score in the L1 post-treatment reading comprehension test, and out-performed the control group who received traditional reading instruction L1. However, the experimental group could not transfer this overall success in L1 reading comprehension to L2 context, and achieved only a limited gain score pertaining to inference skills in the L2 post-treatment reading comprehension test. The cause of this failure was considered as a short-circuiting effect of simultaneous reading strategy instruction in L1 and L2, and the negative outcome of the interference effect of L1 reading approach on L2 reading comprehension performance Meanwhile, the control group achieved slight gain scores in both L1 and L2 post-treatment reading comprehension tests, but those did not prove to be statistically significant. However, the increase in L1 reading comprehension performance was attributed to the positive effect of the L2 reading strategy instruction which was transferred to L1 reading. On the other hand, the results obtained from the Self-evaluation Charts of Reading Strategy Use in L1 and L2 reading revealed that frequency of reading strategy use by both the control group and the experimental group increased remarkably after the treatment. In the light of these findings, limitations of the study were mentioned and some suggestions were made for further research. KISA

Okuma stratejilerinde anadil ve yabancı dil arası aktarım olasılığı Bu çalışma anadilde (Türkçe) ve yabancı dilde (İngilizce) verilen okuma stratejileri eğitiminin öğrencilerin anadilde ve yabancı dilde okuduğunu anlama performanslarına etkisini ve okuma stratejilerinin anadil ve yabancı dil arası aktarımını incelemektedir. Çalışmanın denek grubunu parasız yatılı bir devlet erkek lisesinin son sınıfından orta düzeyde İngilizce öğrenmekte olan kırk öğrenci oluşturmuştur. Yirmişer öğrenciden oluşan iki sınıf rasgele Kontrol Grubu ve Deney Grubu olarak belirlenmiştir. Eğitim süresince kontrol grubu yalnızca İngilizce okuma stratejileri eğitimi alırken deney grubuna eşzamanlı olarak hem İngilizce hem de Türkçe okuma stratejileri eğitimi verilmiştir. Veri toplama araçları olarak eğitim öncesinde verilen Kişisel Bilgiler Anketi ile Okuma Alışkanlıkları ve Tercihleri Anketi, ayrıca hem eğitim öncesinde hem de eğitim sonrasında uygulanan Okuma Stratejileri Kullanımı Öz-Değerlendirme Tablosu ile İngilizce ve Türkçe Okuma Testleri kullanılmıştır. Okuma testlerinin sonuçları SPSS (10.0) T-test kullanılarak analiz edilmiş, anket ve öz-değerlendirme tablolarının verileri ise elde hesaplanarak değerlendirilmiştir. Çalışmadan elde edilen bulgular, anadilde okuma stratejileri eğitimi alan deney grubunun Türkçe okuma son-testinde istatistiksel olarak anlamlı bir başarı artışı göstererek, anadilde geleneksel okuma eğitimi almış olan kontrol grubundan daha başarılı olduğunu ortaya koymuştur. Bununla birlikte, deney grubu anadildeki bu genel okuma başarısını yabancı dildeki okuma performansına aktaramamış, İngilizce son-testinde yalnızca çıkarım yapma becerileriyle sınırlı anlamlı bir başarı artışı kaydedebilmiştir. Bu aksaklığın anadildeki eşzamanlı strateji eğitiminin olumsuz bir aktarımla yabancı dildeki okuma başarısına ket vurmasından kaynaklanmış olabileceği sonucuna varılmıştır. Öte yandan, kontrol grubunun Türkçe son-testinin ayrıntılı bilgi ve çıkarım sorularında elde ettiği istatistiksel olarak anlamlı başarı artışının yabancı dildeki strateji eğitiminin anadildeki okuma performansına sınırlı da olsa aktarıldığı şeklinde değerlendirilmiştir. Ayrıca, Okuma Stratejileri Kullanımı Öz-Değerlendirme Tablosu verileri kontrol ve deney gruplarının anadildeki ve yabancı dilde okuma stratejilerini kullanım sıklığının strateji eğitimi sonrasında önemli oranda arttığını ortaya koymuştur. Sonuçta, elde edilen bulgular ışığında araştırmadaki sınırlayıcı etmenler belirtilmiş ve daha sonraki araştırmalar için bazı öneriler sunulmuştur.
Keywords: Eğitim_Yabancı Dil